2007
DOI: 10.13057/biodiv/d080415
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of antibacteria substances from neem seeds (Azadirachta indica) to impede the growth of Salmonella thyposa and Staphylococcus aureus

Abstract: The effectiveness of antibacteria substances from neem seeds (Azadirachta indica) to impede the growth of Salmonella thyposa and Staphylococcus aureus AMBARWATI ♥

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
4
0
2
Order By: Relevance
“…From the results of the antibacterial activity test, it was found that the fraction of bitter melon leaves (Momordica balsamina L.) had antibacterial activity against Salmonella typhi by forming an inhibition zone around the disc paper of 15.9 mm with a strong antibacterial power category. The results of this study are in accordance with the research of Ambarwati (2007), where the strength of antibacterial power is divided into 4, namely the inhibition zone > 20 mm means very strong, 10-20 mm inhibition zone means strong, 5-10 mm inhibition zone means medium and the inhibition zone < 5 mm or less is weak.…”
Section: Concentration Of Compounds Activesupporting
confidence: 88%
“…From the results of the antibacterial activity test, it was found that the fraction of bitter melon leaves (Momordica balsamina L.) had antibacterial activity against Salmonella typhi by forming an inhibition zone around the disc paper of 15.9 mm with a strong antibacterial power category. The results of this study are in accordance with the research of Ambarwati (2007), where the strength of antibacterial power is divided into 4, namely the inhibition zone > 20 mm means very strong, 10-20 mm inhibition zone means strong, 5-10 mm inhibition zone means medium and the inhibition zone < 5 mm or less is weak.…”
Section: Concentration Of Compounds Activesupporting
confidence: 88%
“…oryzae secara in vitro menggunakan delapan perlakuan yaitu kontrol negative (KON), kontrol positif (KKT), Chitosan (KT) dengan 3 konsentrasi yaitu 0,2%, 0,4%, 0,6 dan Antimicrobial Peptides (AA) dengan 3 konsentrasi 1%, 3%, 5%. Metode yang digunakan dengan Metode Difusi Cakram kertas yang mengacu pada metode Ambarwati (2007); Khoirunnisya (2009). Cakram kertas berbentuk lingkaran dengan diameter 10 mm disterilkan dalam oven.…”
Section: Pendahuluanunclassified
“…This can be seen from its ability to infect humans, animals and plants, causing various diseases from mild infections to death. several pathogenic bacteria that can cause infection such as Staphylococcus aureus, Escherichia coli and Salmonella typhi [1].Infectious diseases are still a serious problem in Indonesia, coupled with the increasing prevalence of microbial resistance to available antibiotic drugs.The World Health Organization has warned of growing antimicrobial resistance during a pandemic. One source of new antibiotics is medicinal plants derived from nature.…”
Section: Introductionmentioning
confidence: 99%